2015
DOI: 10.1371/journal.pgen.1005285
|View full text |Cite|
|
Sign up to set email alerts
|

Necrotic Cells Actively Attract Phagocytes through the Collaborative Action of Two Distinct PS-Exposure Mechanisms

Abstract: Necrosis, a kind of cell death closely associated with pathogenesis and genetic programs, is distinct from apoptosis in both morphology and mechanism. Like apoptotic cells, necrotic cells are swiftly removed from animal bodies to prevent harmful inflammatory and autoimmune responses. In the nematode Caenorhabditis elegans, gain-of-function mutations in certain ion channel subunits result in the excitotoxic necrosis of six touch neurons and their subsequent engulfment and degradation inside engulfing cells. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(111 citation statements)
references
References 92 publications
(149 reference statements)
5
106
0
Order By: Relevance
“…Dominant mutations in mec-4 (the core subunit of a mechanically gated sodium channel) in touch neurons in C. elegans cause hyper channel activity, which results in excess Ca 2+ influx and necrotic cell death. 82,83 Li et al 58 recently showed that necrotic cells in mec-4 nematodes expose PtdSer by the action of ANOH1 (a TMEM16 homolog) and CED7 (an ABCA1-transporter homolog). TNF-induced necroptosis and bacteria-induced pyroptosis are mediated by calcium influx.…”
mentioning
confidence: 99%
“…Dominant mutations in mec-4 (the core subunit of a mechanically gated sodium channel) in touch neurons in C. elegans cause hyper channel activity, which results in excess Ca 2+ influx and necrotic cell death. 82,83 Li et al 58 recently showed that necrotic cells in mec-4 nematodes expose PtdSer by the action of ANOH1 (a TMEM16 homolog) and CED7 (an ABCA1-transporter homolog). TNF-induced necroptosis and bacteria-induced pyroptosis are mediated by calcium influx.…”
mentioning
confidence: 99%
“…These observations are confirmed by other studies in C. elegans Nawa et al 2012) and by a mammalian study in which inactivation of CDC50A, a cofactor for the human TAT-1 homolog ATP11C, causes ectopic PS exposure in living cells and their phagocytosis by macrophages (Segawa et al 2014). The engulfment of living cells by phagocytes in the tat-1 mutants is blocked by lf mutations in PS receptor family 1 (psr-1) and ced-1, two phagocyte receptors that recognize surface-exposed PS and act in two major phagocytosis pathways (Zhou et al 2001b;Wang et al 2003;DarlandRansom et al 2008;Wang et al 2010;Li et al 2015;Yang et al 2015), suggesting that externalized PS can serve as an eat me signal for both engulfment pathways. Mitochondrial elimination: As described above, mitochondria play an important role in regulating cell death execution in C. elegans.…”
Section: Cell Death Executionmentioning
confidence: 99%
“…TTR-52 binds both PS and the extracellular domain of CED-1 in vitro and likely functions as a bridging molecule that mediates recognition of apoptotic cells by cross-linking the exposed PS eat me signal with the engulfment receptor CED-1 ( Figure 2B). In addition, a recent study suggests that the extracellular region of CED-1 could directly bind PS in vitro, when fused to GST (Li et al 2015).…”
Section: Engulfment Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…More recent studies have provided evidence that PS exposure serves as a common “eat-me” signal for cells dying by necrosis and apoptosis [39]. Indeed, in contrast to common belief, PS was actively exposed on the outer surface of touch neurons dying by necrosis prior to the disintegration of the plasma membrane.…”
Section: Conservation Of Cell Clearance Pathways: Focus On Ps Expomentioning
confidence: 99%